Monitoring microcirculation. Issue 4 (December 2016) - Ocak, Işık; Kara, Atila; Ince, Can
Abstract : The clinical relevance of microcirculation and its bedside observation started gaining importance in the 1990s since the introduction of hand-held video microscopes. From then, this technology has been continuously developed, and its clinical relevance has been established in more than 400 studies. In this paper, we review the different types of video microscopes, their application techniques, the microcirculation of different organ systems, the analysis methods, and the software and scoring systems. The main focus of this review will be on the state-of-art technique, CytoCam-incident dark-field imaging, and the most recent technological and technical updates concerning microcirculation monitoring.